Correlation between ldl, hdl, and triglyceride conditions with body fat percentage of universitas padjadjaran professors - Saputra, Yosi Wailan; Miftahurachman, Miftahurachman; Lubis, Leonardo (Folia Medica Indonesiana, 2017)
Elderly is a problem that may disrupt the balance of various molecules in the body, especially fat molecules, which may result in the emergence of various diseases so that blood fat and adipose level examinations need to be done regularly and periodically as an effort of early detection. This study aimed to find correlation between Low Density Lipoprotein (LDL), High Density Lipoprotein (HDL), and triglyceride with body fat percentage among professors in Universitas Padjadjaran (Unpad) who were mostly in elderly age. This study was a linear regression analytical study conducted on 52 Unpad professors (â™‚ 75%, â™€ 25%) based on data of LDL, HDL, and triglyceride levels obtained through laboratory examination, as well as body fat percentage data by using Bio Impedance Analysis (BIA). The correlation between low density lipoprotein (LDL), High Density Lipoprotein (HDL), and triglyceride with body fat percentage in male professors group was R2=0.072; P>0.05 and in female was R2=0.028; P>0.05. As a conclusion, there was no correlation between Low Density Lipoprotein (LDL), High Density Lipoprotein (HDL), and triglyceride with body fat percentage in Unpad professors.